Evaluation Method of Movable Shale Oil Resource: A Case Study of the Shahejie Formation in the Dongying Sag, Jiyang Depression - Xu, Liang; Wang, Min; Li, Jinbu; Li, Ming; Li, Zheng; Zhu, Rifang; Liu, Huimin (Frontiers in Earth Science, 2021)
Although China has enormous shale oil resource potential, oil recovery is limited at present, largely because its movable resource is not evaluated. In this study, an evaluation method for movable shale oil resources is proposed. The process first evaluates the total shale oil resource (Qtotal), and then two-dimensional nuclear magnetic resonance (NMR) technology is used to measure the free oil ratio (Rfree) and further define the quantitative relationship (F) between the movable ratio (Rm) in the free oil and centrifugal force. The movable oil resource is calculated by the total shale oil resource, free oil ratio, and movable oil ratio (Qm = Qtotal × Rfree × Rm). This method was applied to the Shahejie Formation of the Dongying Sag, Jiyang Depression, in Bohai Bay Basin, and the relationship between the free oil ratio (Rfree) and depth was established based on several core 2D NMR data. Based on the formation pressure, flowing bottom hole pressure, and relationship (F), the movable shale oil ratio (Rm) in the target area was determined. The results showed that the movable shale oil ratio (Rm) of the lower Es3 is approximately 18.9–20% in the depth range of 3200–3700 m, and the movable shale oil resource is approximately 2.52 × 108 t.